Impact of Supply Chain Management Strategy on PerformanceOperations in Micro, Small and Medium Enterprises - Pratiwi, Nurul Aziz (Management Studies and Business Journal (PRODUCTIVITY), 2024)
The Indonesian economy is significantly influenced by Micro, Small, and Medium Enterprises (MSMEs), which are the main support for the country's economy.. Therefore, the aim of this research is to identify the impact of supply chain management strategies on the operational performance of MSMEs. Data was collected by questionnaires distributed to 151 respondents, and testing was carried out using the Structural Equation Method (SEM). The findings of the study reveal that the operational performance of MSMEs is not impacted by all implemented supply chain management strategies. Out of the five supply chain management strategies, not all exhibit a significant effect. employed, one of them is not demonstrated to have a significant impact on the operational performance of a business.